The Use of Digital Folklore as a Medium for Teaching Indonesian to Instill Values in Elementary Schools - Slamet Slamet; Lilik Binti Mirnawati; Fajar Setiawan (Yayasan Citra Dharma Cindekia, 2026)
This study aims to describe the use of digital folklore media